Unequal childhoods : young children's lives in poor countries - Penn, Helen (Contesting early childhood., 2005)
While problems of childhood poverty are most widespread in developing countries, formidable inequalities exist in more prosperous countries. A major aim of the book is to address the question of unequal childhoodsand the ways in which they are.